Многокритериальная оптимизация проектных вариантов при планировании сетей LTE - Безрук, В. М.; Иваненко, С. А.; Чеботарёва, Д. В. (ХНУРЭ, 2013)
New stage of development of mobile wireless networks 4G network. Examines the use of technology LTE as the most promising implementation of the concept of 4G. The network of this generation характеризуються higher band-width, full convergence with wired IP networks, adaptive management of the frequency spectrum and high quality of service for multimedia traffic. Currently it is rather important question is the planning and optimization of communication networks 4G. First, if the methods of planning of mobile communication networks of previous generations are well developed, for 4G networks they are on the stage of development. Secondly building networks 4G is very costly, which does not allow to con-duct large-scale experiments to build a network in real conditions. Defines the main aspects of planning LTE networks. The advantages obtained by using technology OFDM and MIMO. Also provides basic method of estimating the efficiency of projected networks. Provides the basic tasks and methods of selection of optimal design options when planning for mobile networks based on LTE technology. Analysis of the frequency spectrum of Ukraine, with the purpose of introduction of LTE technology.